2015
DOI: 10.3389/fphar.2015.00202
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal regulation of cAMP signaling controls the human trophoblast fusion

Abstract: During human placentation, mononuclear cytotrophoblasts fuse to form multinucleated syncytia ensuring hormonal production and nutrient exchanges between the maternal and fetal circulation. Syncytial formation is essential for the maintenance of pregnancy and for fetal growth. The cAMP signaling pathway is the major route to trigger trophoblast fusion and its activation results in phosphorylation of specific intracellular target proteins, in transcription of fusogenic genes and assembly of macromolecular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 82 publications
1
27
0
Order By: Relevance
“…Finally, AKAPs bind to or co-localize with specific PKA substrates to allow rapid and efficient phosphorylation [25]. Several AKAPs have been described in human placenta and we recently showed that two or more AKAPs are involved in the regulation of trophoblast fusion [20,[28][29][30]. Specifically, ezrin establishes a signaling complex with PKA and connexin 43 (Cx43) that mediates gap junction communication and thereby triggers trophoblast fusion [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, AKAPs bind to or co-localize with specific PKA substrates to allow rapid and efficient phosphorylation [25]. Several AKAPs have been described in human placenta and we recently showed that two or more AKAPs are involved in the regulation of trophoblast fusion [20,[28][29][30]. Specifically, ezrin establishes a signaling complex with PKA and connexin 43 (Cx43) that mediates gap junction communication and thereby triggers trophoblast fusion [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…This process of syncytialization is a hallmark of placentation and plays a central role in physiological function of the placental barrier as a key regulator of material exchange between the maternal and fetal circulations 23 . While the underlying molecular pathways of syncytialization are not fully understood, studies have shown that activation of adenylate cyclase, which is the regulatory subunit of protein kinase A, by 3′,5′-cyclic monophosphate (cAMP) or forskolin induces BeWo cells and primary villous cytotrophoblast cells to fuse and acquire differentiated phenotypes of the syncytiotrophoblast 24,25 .…”
Section: Resultsmentioning
confidence: 99%
“…The role of P-gp in trophoblast fusion is less surprising as a number of studies have reported the loss or down-regulation of P-gp in the spontaneous differentiation of primary CT to ST. [40][41][42] It is also well known that trophoblast fusion stimulated by the protein kinase A pathway and cAMP involves the induction of GJA1 and hCG. 43 Knockdown of their expression in the BeWo choriocarcinoma model results in an arrest of forskolin-stimulated fusion, 44,45 while overexpression of Cx43 permits Jeg-3 cell fusion. 28 As a point of speculation, beyond its well-known role in substrate distribution and bioavailability and in multidrug resistance, P-gp plays a role in cancer cell invasion, drug resistance and metastasis.…”
mentioning
confidence: 99%